CONSTITUTION, CIVIL SOCIETY AND THE FIGHT AGAINST RADICALISM: THE EXPERIENCE OF INDONESIA AND AUSTRIA - Asfa Widiyanto (Analisa: Journal of Social Science and Religion, 2016)
The German scholar Ernst-Wolfgang Böckenförde (b. 1930) is reported to have said that “the free secular state lives on premises that it cannot itself guarantee”. These premises include the morality, commitment to public order and the like. In this train of thought, we may say that the constitution is in need of strong civil society so as to maintain the well-being of the state. This article employs documents, observation and interviews to highlight the experience of Indonesia and Austria in minimizing radicalism. The first concern of this paper deals with the interplays between constitution and civil society in eradicating radical tendencies within Indonesian and Austrian society, most particularly within the Muslim communities of these respective countries. The second concern of the paper delves in which ways expressions of Islam in Indonesia and Austria contribute to the making of peace in the respective societies. Islam is recognized as religion in both countries. The notions of “European Islam” and “Indonesian Islam” are believed to shape the current-state of eradicating radicalism in the two countries.